2003
DOI: 10.1080/0265203021000055379
|View full text |Cite
|
Sign up to set email alerts
|

Mercury, arsenic, lead and cadmium in fish and shellfish from the Adriatic Sea

Abstract: The aim was to measure concentrations of total mercury, total arsenic, lead and cadmium in common edible fresh fish and shellfish from various areas of the Adriatic Sea. Estimates of intake of these elements were made through seafood consumption by the general population. Samples were either wet digested for mercury and arsenic, or dry ashed for lead and cadmium analysis. Mercury was measured by cold vapour atomic absorption spectrometry (CV AAS) and arsenic, lead and cadmium by electrothermal atomic absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 13 publications
7
43
3
Order By: Relevance
“…The lack of relationships is in line with findings of Besada et al (2006) for a broader range of sizes of T. obesus, T. alalunga and T. albacores captured in the Atlantic Ocean. Previous studies with other fish species from the Adriatic and Mediterranean also conclude that size has no effect on trace element accumulation in muscle and liver (Canli and Atli, 2003;Juresa and Blanusa, 2003). Figure 2 showed that partitioning among tissues varied with the studied elements.…”
Section: Resultsmentioning
confidence: 78%
“…The lack of relationships is in line with findings of Besada et al (2006) for a broader range of sizes of T. obesus, T. alalunga and T. albacores captured in the Atlantic Ocean. Previous studies with other fish species from the Adriatic and Mediterranean also conclude that size has no effect on trace element accumulation in muscle and liver (Canli and Atli, 2003;Juresa and Blanusa, 2003). Figure 2 showed that partitioning among tissues varied with the studied elements.…”
Section: Resultsmentioning
confidence: 78%
“…Once PEPs are ingested, they are distributed to different tissues in organisms, depending on the lipid content. The liver and gonads are the most contaminated, whereas muscle is generally less contaminated [17,21,61]. However, muscle is commonly analyzed because it is the main fish part consumed by humans.…”
Section: Factors Affecting the Occurrence Of Peps In Seafoodmentioning
confidence: 99%
“…Tuzen [6] had measured an arsenic concentration in different fish species from Black Sea as follows: 0.15 ± 0.01 μg/g for Psetta maxima; 0.27±0.02 μg/g for Pomatomus saltator, 0.23±0.01 μg/g for Mugil cephalus, 0.14±0.01 μg/g for Sarda sarda, 0.18±0.02 μg/g for Trachurus trachurus and 0.17±0.01 μg/g for Sprattus sprattus. The concentration of arsenic reported in fish species from Adriatic Sea ranged of 0.56 to 10.03 mg/kg fresh weight [19] and up to 1.74 μg/g w.w. in the muscle of S. Lascaris in Turkish part of the Black Sea [1].…”
Section: Essential Elementsmentioning
confidence: 99%
“…In our previous study on heavy metal pollution in muscle tissue of bluefish, the cadmium levels were below 0.07 mg/kg fresh weight [18]. Cadmium concentration in literature has been reported as follow: 0.02-0.37 mg/kg for edible part of fishes caught from Marmara, Aegean and Mediterranean seas in Turkey [17] and 0.002-0.02 mg Cd kg -1 fresh weight for species from Adriatic Sea [19].…”
Section: Essential Elementsmentioning
confidence: 99%